Cooperation Between Active Metal and Basic Support in Ni-Based Catalyst for Low-Temperature CO2 Methanation - Ma, Yuan; Liu, Jiao; Chu, Mo; Yue, Junrong; Cui, Yanbin; Xu, Guangwen (Catalysis letters, 2020)
The key challenge for CO 2 methanation, an eight-electron process under kinetic limitation, relies on the design of non-noble metal catalysts so as to achieve high activity at low reaction temperatures. In this work, four Ni-based catalysts with different supports were prepared and tested for CO 2 methanation at 250–550 °C in a fixed bed quartz reactor and further characterized to reveal the structure–function relationship. The Ni-based catalysts followed an activity order of Ni/CeO 2 > Ni/Al 2 O 3 > Ni/TiO 2 > Ni/ZrO 2 , especially at temperatures lower than 350 °C. H 2 -TPR and TPD results indicated that the interaction between nickel and support was strong and the metallic nickel was well dispersed in the Ni/Al 2 O 3 catalyst, while more amount of CO 2 was adsorbed on the weak basic sites in the Ni/CeO 2 catalyst. By establishing the correlation between the catalytic performance and the catalyst structure, it was found that the Ni nanoparticles and basic support serve as H 2 and CO 2 active centers respectively and cooperatively catalyze CO 2 methanation, resulting in high low-temperature reaction activity. Graphic Abstract High CO 2 conversion was achieved over Ni/CeO 2 catalyst at 300 °C for its high H 2 uptake on Ni nanoparticles and high CO 2 adsorption capacity on the support with weak basic sites and cooperatively to catalyze CO 2 methanation.